Historical commentary on the Pastoral Epistles - Ramsay, William Mitchell, 1851-1939; Wilson, Mark (Grand Rapids, MI Kregel, 1996)
Includes bibliographical references.
Previously "published in the Expositor, seventh series, 7 and 8 (1909); 9 (1910); Eighth series, 1 (1911)" [intro.]
Keywords: Bible. N.T. Pastoral Epistles -- commentaries